The implementation of mobile internet protocol in local area network - 232948 Norsheila Fisal; Lee, Soon Ho; Yazid Mohamed; National Conference on Telecommunication Technology 2000 (2000 : Johor Bahru) (Skudai : Universiti Teknologi Malaysia, 2000)
13